In vitro study of resveratrol as an antioxidant for boar semen preservation: A systematic review - Ragil Angga Prastiya; Trilas Sardjito; Amung Logam Saputro; Sari Yanti Hayanti; Nining Haryuni; Samira Musa Sasi (Veterinary World)
Background and Aim: In the global pig farming industry, artificial insemination (AI) is widely used to propagate high-quality genetics using processed semen that can be stored for extended periods. However, boar sperm are particularly susceptible to oxidative damage during storage and cryopreservation because of their high polyunsaturated fatty acid content. This study aimed to systematically review the impact of resveratrol (RVT), a potent antioxidant, on the preservation of boar semen.